On the papers of M.I. Yadrenko on the theory of random fields - Buldygin, V.V.; Kozachenko, Yu.V.; Leonenko, N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A survey of the works of M. I. Yadrenko in the theory of random fields on finite-dimensional and infinite-dimensional spaces is presented.